FINANCIAL TECHNOLOGY AND IT’S IMPACT ON MSMEs IN CHOOSING BANK CREDIT SERVICES IN JAMBI - Eka Julianti Efris Saputri; Fitri Chairunnisa (Management Department, Faculty of Economics and Business, Universitas Jambi, 2021)
Fintech supports the implementation of electronic applications, one of which is access to financial inclusion, this is evident from the increasing financial inclusion in Indonesia, one of which is in Jambi City. Until 2018, the development of bank credit debit trays in Indonesia continued to increase. With the presence of fintech companies in Indonesia, several SMEs who were met admitted to applying for credit in addition to using bank credit services, namely applications launched by Fintech companies. This type of research is descriptive qualitative. The data collection method in this research is by distributing questionnaires and conducting interviews with correspondents. By using logistic regression, the purpose of this study is to determine the factors that influence SMEs in choosing bank credit services in Jambi City with the presence of financial technology. The results are only a few factors that influence SMEs in choosing bank credit services in Jambi.